Association between red blood cell distribution width to albumin ratio and periodontitis in US adults - Lina Zhu; Ke Yang; Qian Zheng; Wenhao Qian (Medicine, 2026)
Research on the potential relationship between RAR and periodontitis remains unclear. This study examines the association between RAR and periodontitis among US adults, utilizing data from the National Health and Nutrition Examination Survey (NHANES; 2009–2014). Weighted multivariate logistic regression analyses, restricted cubic spline curve (RCS) models, and subgroup analyses were utilized to evaluate the relationship between RAR and periodontitis. Additionally, sensitivity analysis was used to evaluate the robustness of the results. This study included 8529 participants, 3928 (46.05%) with moderate or severe periodontitis. After full adjustment for potential confounders, RAR was significantly associated with periodontitis (OR = 1.23, 95% CI: 1.02–1.49). When RAR were categorized as 4 groups, periodontitis were possibly associated with Q2 (OR = 1.02, 95% CI: 0.86–1.21), Q3 (OR = 1.31, 95% CI: 1.09–1.58), Q4 (OR = 1.21, 95% CI: 0.95–1.54). The RCS models indicated a nonlinear association between RAR and periodontitis ( P < .001). Additionally, subgroup analyses and sensitivity analyses validated the robustness of the finding regarding the association. This study suggests that higher RAR level was associated with higher odds of periodontitis.